The Relationship Between Husband's Support and Pregnant Women's Willingness to Provide Exclusive Breastfeeding at the Eka Sriwahyuni Clinic in 2025 - ‎, Masni; Br. Saragih, Pebrinawanti; ‎, Ruseni; ‎, Tisnilawati; Lubis, Rhina Chairani; Nurmaliza, Lili (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Exclusive breastfeeding is breast milk given to babies for six months, without adding formula milk, orange juice, honey, sugar water, without solid foods such as bananas, porridge, milk and rice (except medicines, vitamins and minerals).The purpose of this study was to determine the relationship between husband's support and the willingness of pregnant women to provide exclusive breastfeeding at the Eka Sriwahyuni Clinic in 2025. The study was cross-sectional with primary data obtained directly from the questionnaire, the population in this study were all pregnant women who visited the Eka Sriwahyuni clinic with a total of 30 respondents. The sampling technique in this study used the accidental sampling method. Data analysis used univariate analysis and bivariate analysis. The results of this study indicate a relationship between husband's support and the willingness of pregnant women to provide exclusive breastfeeding at the Eka Sriwahyuni clinic in 2025 with the results obtained using the chi-square test with a p-value of0,000shows that the p-value <0.05 means that there is a relationship between husband's support and the pregnant mother's willingness to provide exclusive breastfeeding.The conclusion of this study is that the husband's support that mothers receive in exclusive breastfeeding has a positive effect on the mother's experience, which influences the amount of breast milk produced by the mother because breast milk production becomes smoother.